1997
DOI: 10.1074/jbc.272.24.15258
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the Gene Coding for the Antibacterial Peptide LL-37 Is Induced in Human Keratinocytes during Inflammatory Disorders

Abstract: The epithelia constitute a major barrier to the environment and provide the first line of defense against invading microbes. Antimicrobial peptides are emerging as participants in the defense system of epithelial barriers in general. Originally we isolated the human antimicrobial peptide LL-37 from granulocytes. The gene (CAMP or cathelicidin antimicrobial peptide) coding for this peptide belongs to the cathelicidin family, whose members contain a conserved pro-part of the cathelin type. The human genome seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
624
3
11

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(651 citation statements)
references
References 22 publications
9
624
3
11
Order By: Relevance
“…This is consistent with a role for LL-37 in antimicrobial barrier protection in human and agrees with earlier reports where low constitutive expression of LL-37 was found in normal quiescent epithelium, in contrast to the pronounced expression seen in association with injury and inflammation. [7][8][9][10] Constitutive expression of antimicrobial peptides has previously been detected in various exocrine glands such as the human cathelicidin LL-37 in sweat glands, the cathelicidin CRAMP in murine salivary glands and ␤-defensins in human salivary glands. [21][22][23] Expression of human ␤-defensin-2 (hBD-2) mRNA in mammary glands was reported by Bals et al 24 in 1998 and recently other groups have found constitutive hBD-1 expression in mammary glandular tissue of nonlactating women as well as in breast tissue during lactation and in breast milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a role for LL-37 in antimicrobial barrier protection in human and agrees with earlier reports where low constitutive expression of LL-37 was found in normal quiescent epithelium, in contrast to the pronounced expression seen in association with injury and inflammation. [7][8][9][10] Constitutive expression of antimicrobial peptides has previously been detected in various exocrine glands such as the human cathelicidin LL-37 in sweat glands, the cathelicidin CRAMP in murine salivary glands and ␤-defensins in human salivary glands. [21][22][23] Expression of human ␤-defensin-2 (hBD-2) mRNA in mammary glands was reported by Bals et al 24 in 1998 and recently other groups have found constitutive hBD-1 expression in mammary glandular tissue of nonlactating women as well as in breast tissue during lactation and in breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Extracellular proteolytic processing of the holoprotein releases the LL-37 peptide, which has broad antimicrobial activity 1,3 as well as effects on host cells mediated by the G-protein-coupled receptor, formyl peptide receptor-like 1 (FPRL1). 4,5 hCAP18 is present in leucocytes 6 and is expressed in skin and other epithelia, where it is upregulated in association with inflammation 7,8 and injury, 9,10 consistent with a role in innate barrier protection. Recently, antimicrobial proteins including cathelicidins have been proposed to play a role also in the nonspecific host defense against tumors.…”
mentioning
confidence: 97%
“…It has been detected in leukocytes, such as neutrophils, monocytes, NK cells, gd cells, B cells and in the epithelial cells of the testis, the gastrointestinal and respiratory tracts and in inflamed skin as an inactive pro form. [10][11][12] Extracellular cleavage into a cathelinlike domain of 14.3 kDa and the 37-amino-acid-long C-terminus (LL-37) activates the pro peptide, which by its own has been identified in plasma, airway surface fluid and in wound secretions. 10,11,13 The peptide is induced by pro-inflammatory infectious stimuli and displays direct antimicrobial activity by interaction with the cell membranes of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Extracellular cleavage into a cathelinlike domain of 14.3 kDa and the 37-amino-acid-long C-terminus (LL-37) activates the pro peptide, which by its own has been identified in plasma, airway surface fluid and in wound secretions. 10,11,13 The peptide is induced by pro-inflammatory infectious stimuli and displays direct antimicrobial activity by interaction with the cell membranes of microorganisms. 14 Primarily understood as endogenous antibiotics, HDP obtain increasing importance as multifunctional mediators in the complex responses of innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…LL37/hCAP18 is initially synthesized as an 18 kD protein; then during and after secretion, it is processed to the mature 5 kD peptide (37 amino acid residues) [90,91]. LL37/hCAP18 has been identified in neutrophils, monocytes, various epithelial cells, saliva, sweat glands, and other tissues [90][91][92][93][94][95][96]. The peptide has a linear form, resembling an alpha helical structure.…”
Section: Defensinsmentioning
confidence: 99%